Optimization of Pulse Laser Annealing to Increase Sharpness of Implanted-junction Rectifier in Semiconductor Heterostructure - Pankratov, E. L. (Nano-Micro Letters, 2010)
It has been recently shown that inhomogeneity of a semiconductor heterostructure leads to increasing of sharpness of diffusion-junction and implanted-junction rectifiers, which are formed in the semiconductor heterostructure. It has been also shown that together with increasing of the sharpness, homogeneity of impurity distribution in doped area increases. The both effect could be increased by formation of an inhomogeneous distribution of temperature (for example, by laser annealing). Some conditions on correlation between inhomogeneities of the semiconductor heterostructure and temperature distribution have been considered. Annealing time has been optimized for pulse laser annealing.